JURIDICAL ANALYSIS OF FORCE MAJEURE CONDITIONS AS A REASON FOR THE FAILURE TO PERFORM THE CONTENTS OF THE AGREEMENT BY THE LESSOR (A STUDY OF DECISION NUMBER 130/Pdt.G/2023/PN.Mdn) - Maria Simamora; Roida Nababan; Besty Habeahan (RADJA PUBLIKA, 2026)
The occurrence of force majeure in an agreement gives rise to legal consequences concerning the performance of the parties’ obligations and potential losses arising from the agreement. In practice, force majeure is often invoked as a defense to avoid liability for breach of contract, including in lease agreements. In Decision Number 130/Pdt.G/2023/PN Mdn, the defendant failed to carry out the agreed renovation of a commercial building and invoked the Covid-19 pandemic as force majeure. This claim raises legal issues regarding whether the elements of force majeure were fulfilled and the limits of the legal liability borne by the invoking party. The aim of the present research is to evaluate the application of force majeure as a defense against contract violations and to look at the judges' legal rationale in reaching their decision. The study is descriptive in nature, applying a normative legal approach with statute and case approaches, and is qualitatively investigated through library research. Since there is no causal connection between the Covid-19 pandemic and the renovation obligation that was due before it happened, the findings show that the pandemic does not meet the requirements of force majeure as outlined in Articles 1244 and 1245 of the Indonesian Civil Code. The defendant’s financial difficulties were categorized as business risks. The decision reaffirms the principles of pacta sunt servanda, good faith, and the burden of proof on the party invoking force majeure. Keywords: Lease Agreement, Breach of Contract, Force Majeure